INSTALLATION ON THE PERCEPTION OF MUSICAL WORKS IN THE PROFESSIONAL TRAINING OF A FUTURE MUSIC TEACHER (Web of Teachers: Inderscience Research, 2023)
The article discusses the installation on the perception of musical works in the professional training of a future music teacher.